2020
DOI: 10.1016/j.ijsu.2020.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation and hepatobiliary surgery in 2020

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Liver transplantation (LT) has become a standard therapy for patients with end-stage liver disease and fulminant liver failure. Postoperative morbidity still remains high, [1] especially when accounting for vascular complications. [2,3] Hepatic artery thrombosis (HAT) occurs in 4%-9% of adult LT [4,5] and is one of the most serious vascular complications often resulting in liver necrosis, abscess formation, ischemic cholangiopathy, and graft loss.…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation (LT) has become a standard therapy for patients with end-stage liver disease and fulminant liver failure. Postoperative morbidity still remains high, [1] especially when accounting for vascular complications. [2,3] Hepatic artery thrombosis (HAT) occurs in 4%-9% of adult LT [4,5] and is one of the most serious vascular complications often resulting in liver necrosis, abscess formation, ischemic cholangiopathy, and graft loss.…”
Section: Introductionmentioning
confidence: 99%
“…There are significant challenges with liver transplantation in patients with PSC including (I) technical difficulties, (II) recurrent cholangitis post-liver transplantation due to an immunosuppressive state, (III) increased risk of rejection due to the autoimmune nature of the disease, (IV) recurrence of the disease post-liver transplantation, and (V) the shortage of liver allografts which necessitates the use of extended criteria and donation after circulatory death grafts. Despite these challenges, the post-liver transplant graft and patient survival in patients with PSC is similar to non-PSC patients ( 2 - 6 ).…”
mentioning
confidence: 99%
“…Although the authors concluded that morbidity measured with a 1-year CCI score appeared to significantly affect the 1-year patient survival, in the long-term, morbidity measured with an overall CCI score appeared to be mainly increased by low-grade complications, such as infections and hypertension. However, we wonder if studies that span over 36 years could accurately assess and compare morbidity when the management of PSC gets better over decades by expert hepatologists, better and novel knowledge, such as the impact of gut microbiota ( 10 , 11 ), and better surgeons with improved techniques and knowledge in liver transplantation ( 6 ).…”
mentioning
confidence: 99%
“…Living donor liver transplantation (LDLT) and hepatobiliary surgery require advanced planning to guarantee the maximum safety of living liver donors and patients who undergo major hepatectomy and bile duct surgery 4 . Therefore, the application of deep-learning to LDLT and hepatobiliary surgery would be very helpful in order to guarantee patient safety and better outcomes following liver transplantation.…”
mentioning
confidence: 99%